FEATURES OF USING UNMANNED AERIAL VEHICLE FOR INCREASING POSSIBILITY OF UNIT'S COMBAT CAPABILITIES (Margalla Papers, 2020)
This article deals with topical issues of increasing capabilities, Upgrading combat capabilities, forces and intelligence equipment through the introduction of unmanned aerial vehicles. Examples of tactically and technically effective models of unmanned aerial vehicles, their advantages and calculations to increase the probability of detecting an enemy object are given. Bibliography EntryAkshlakov, K., G. Baiseitov, A. Boiko, and A. Temirbekuly. 2020. "Features of Using Unmanned Aerial Vehicle for Increasing Possibility of Unit's Combat Capabilities." Margalla Papers 24 (2): 133-138.